1990
DOI: 10.3758/bf03211521
|View full text |Cite
|
Sign up to set email alerts
|

Auditory psychomotor coordination and visual search performance

Abstract: In Experiments 1 and 2, the time to locate and identify a visual target (visual search performance in a two-alternative forced-choice paradigm) was measured as a function of the location of the target relative to the subject's initial line of gaze. In Experiment 1, tests were conducted within a 260°region on the horizontal plane at a fixed elevation (eye level). In Experiment 2, the position of the target was varied in both the horizontal (260°) and the vertical (±46°from the initial line of gaze) planes. In b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
109
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 17 publications
(12 reference statements)
10
109
2
1
Order By: Relevance
“…One approach to quantifying the performance advantage afforded by the use of spatial audio displays is to investigate the reduction in search times obtained when such displays are used in a target acquisition task. This can be accomplished using the aurally aided visual search paradigm developed by Perrott, Saberi, Brown, and Strybel (1990).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to quantifying the performance advantage afforded by the use of spatial audio displays is to investigate the reduction in search times obtained when such displays are used in a target acquisition task. This can be accomplished using the aurally aided visual search paradigm developed by Perrott, Saberi, Brown, and Strybel (1990).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that both the visual system (Finlay, 1982;To, Regan, Wood, & Mollon, 2011) and the auditory system (Grantham, 1986) are most accurate in tracking motion parameters in the central field, and that this accuracy decreases in both modalities when attempting to track moving targets in paralateral and lateral space. However, accuracy across space is not comparable between the two modalities (Perrott, Ambarsoom, & Tucker, 1987;Perrott, Saberi, Brown, & Strybel, 1990) because visual resolution is superior to auditory resolution in central space, but declines more severely than auditory resolution toward lateral space. That is, the visual function crosses below the shallower slope of the auditory function.…”
mentioning
confidence: 99%
“…Under such conditions, the presentation of spatially informative cues may offer an effective means not only of reducing the time needed to detect potential threats but also of improving the subsequent discrimination of those threats. The presentation of spatially informative nonvisual cues-specifically, auditory cues that are colocalized with visual targets-has been shown to reduce visual search latencies by several thousand milliseconds for peripherally located visual targets (i.e., for targets presented at eccentricities exceeding 90º from central fixation; see, e.g., Perrott, Cisneros, McKinley, & D'Angelo, 1996;Perrott, Saberi, Brown, & Strybel, 1990;Perrot, Sadralodabai, Saberi, & Strybel, 1991). The p presentation of spatially uninformative auditory cues has also been shown to reduce visual search latencies for vin sual targets presented in the central field by more than 200 msec (e.g., Dufour, 1999;Perrott et al, 1996;Perrott et al, 1991).…”
mentioning
confidence: 99%